1996
DOI: 10.1117/12.233373
|View full text |Cite
|
Sign up to set email alerts
|

Cell damage by UVA radiation of a mercury microscopy lamp probed by autofluorescence modifications, cloning assay, and comet assay

Abstract: Cell damage by low-power 365-nm radiation of a 50-W high-pressure mercury microscopy lamp was studied. Exposure of Chinese hamster ovary (CHO) cells to ultraviolet-A (UVA) radiation Ͼ10 kJ/m 2 resulted in significant modifications of nicotinamide adenine dinucleotide (NADH) attributed autofluorescence and inhibition of cell division. Single-cell gel electrophoresis (comet assay) revealed UVA-induced single-strand DNA breaks. According to these results, UVA excitation radiation in fluorescence microscopy may da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The accumulation of these molecular species highlights a condition of metabolic impairment, due to the dysfunction of mitochondrial electron transport [24]. The increase of NAD(P)Hb by comparing the wavelength ratios (450/480, 450/525, and 480/525 nm), is consistent with the efflux of the coenzyme from mitochondria, its diffusion and aspecific binding to cytoplasmic and nuclear proteins [23].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The accumulation of these molecular species highlights a condition of metabolic impairment, due to the dysfunction of mitochondrial electron transport [24]. The increase of NAD(P)Hb by comparing the wavelength ratios (450/480, 450/525, and 480/525 nm), is consistent with the efflux of the coenzyme from mitochondria, its diffusion and aspecific binding to cytoplasmic and nuclear proteins [23].…”
Section: Discussionmentioning
confidence: 73%
“…5C), might be attributed to membrane damage, thus explaining the diffuse fluorescence haloes observed in hypogravity cells. It is known that membrane damage causes the leakage of coenzyme molecules, as NAD(P)H and flavins from mitochondria, and their diffusion in all the parts of the cell, nucleus included [11,23]. Under 365 nm excitation, the visible autofluorescence is mainly due to NAD(P)H, blue component, and oxidized flavins, yellow-green component [15].…”
Section: Discussionmentioning
confidence: 99%
“…Our results also show that the arrest is not due to alterations in the culture medium, as unimaged embryos in the same drop remain viable. Cellular damage caused by light has been shown in other cell types for various wavelengths, ranging from 295 to 500 nm (one photon) 22,23 or 730 nm to 800 nm (two photons) 17 . Therefore, we sought to determine a possible endogenous source of this phototoxicity.…”
mentioning
confidence: 99%
“…For a given excitation intensity, UV light is more toxic than visible or near-infrared (NIR) light because there are a variety of endogenous fluorescent species present in cells that can absorb UV light and sensitize ROS production, including flavins, NAD(P)H and porphyrins. 108 For example, Gorgidze et al observed wavelength-dependent, mitotic inhibition in pig kidney embryo cells with near-UV (360 nm) light being 5 times more inhibitory than blue light (423–488 nm) and >50 times more inhibitory than green light (>500 nm). 109 …”
Section: Photoxicity Of Uv Excitation Light Used In Lanthanide Imagingmentioning
confidence: 99%